Natural products : discourse, diversity and design - Osbourn, Anne E.; Goss, Rebecca J. (Ames, Iowa ; Chichester, West Sussex, UK : John Wiley & Sons, 2014)
"Natural Products: Discourse, Diversity and Design provides an informative and accessible overview of discoveries in the area of natural products in the genomic era, bringing together advances across the kingdoms. As genomics data makes it increasingly clear that the genomes of microbes and plants contain far more genes for natural product synthesis than had been predicted from the numbers of previously identified metabolites, the potential of these organisms to synthesize diverse natural products is likely to be far greater than previously envisaged. Natural Products addresses not only the philosophical questions of the natural role of these metabolites, but also the evolution of single and multiple pathways, and how these pathways and products may be harnessed to aid discovery of new bioactives and modes of action. Edited by recognized leaders in the fields of plant and microbial biology, bioorganic chemistry and natural products chemistry, and with contributions from researchers at top labs around the world, Natural Products is unprecedented in its combination of disciplines and the breadth of its coverage. Natural Produces: Discourse, Diversity and Design will appeal to advanced students and experienced researchers, from academia to industry, in diverse areas including ecology, industrial biotechnology, drug discovery, medicinal chemistry, agronomy, crop improvement, and natural product chemistry"--Provided by publisher.
Natural products in the natural world -- Role and reason -- Self-protection: avoiding autotoxicity -- Fishing and pharming -- From genes to molecules -- Reading the genome -- Biosynthesis and heterologous expression -- Regulation: waking sleeping pathways -- Evolving enzymes, evolving pathways: synthetic biology -- Chemical diversification -- Evolving pathways -- Synthetic biology -- Screening for bioactivity -- Image-based screening approaches to natural products discovery -- Making sense of structures by utilizing Mother Nature's chemical libraries as leads to potential drugs -- Is there an ideal d1atabase for natural products research? -- To application -- Case studies.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Natural products; Biological products; SCIENCE -- Life Sciences -- Biology; Biological products; Natural products; Biological Factors; Microbiological Phenomena -- genetics; Biochemical Phenomena -- genetics; Drug Discovery; Synthetic Biology -- methods; Electronic books